PENDIDIKAN KARAKTER : Strategi Guru Dalam Pembentukan Karakter Nubuwwah Pada Siswa di Aqobah International School Jombang - Zhulaikah, Nur Laila (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Character can be interpreted as innate, heart, soul, personality, character, behavior, personality, nature, character, temperament, and character. For the discussion of the term character in Islam, it is related to the characteristics of the Prophet Muhammad SAW the uswatun hasanah, among the noble characteristics of the Prophet Muhammad are the characteristics of Shiddiq, amanah, fathonah, and tabligh. Teachers as educators are also expected to have the right strategy in shaping the character of students. This study aims to: (1) find out the description of the Nubuwwah Character as a teacher strategy in character building for students at Aqobah International School Jombang (2) find out the supporting and inhibiting factors in the implementation of the Nubuwwah Character formation strategy (3) find out the implications of the teacher's strategy in the formation of Nubuwwah Character in students at Aqobah International School Jombang The approach used in this research is a qualitative approach and the type of descriptive research. Primary data sources were taken from teachers at Aqobah International School Jombang, principals, teachers in the curriculum field, class X students. Data collection techniques in this study were based on interviews, observation and documentation. The data analysis technique uses the theory of Miles and Huberman. The results of this study indicate that: (1) the strategies used by teachers both in the field of subjects and in the field of curriculum a. Using appropriate learning media, b. Using exemplary methods, c. Training students' discipline during learning, d. Using school specialization/extracurricular methods, 5) Establishing open relationships (2) Nubuwwah character reflected in the learning process, namely Siddiq: Contribution spirit, honest in work, Amanah: Responsible for assignments or assignments, on time, Fathonah: Able to digest material (responsive), Tabligh: Communicative, helping friends, (3) Supporting factors of the application of teacher strategies in shaping the character of Nubuwwah in students include easy access to technology, teacher resources, system management at Aqobah International School Jombang, while the inhibiting factors include: come from the students themselves and the technical problems in implementing the strategy. Abstrak Guru sebagai pendidik sekaligus diharapkan memiliki strategi yang tepat dalam membentuk karakter kepada siswa.Untuk bahasan istilah karakter dalam agama Islam dihubungkan kepada sifat-sifat Rasulullah Muhammad SAW sang uswatun hasanah , diantara sifat atau karakter mulia Rasulullah SAW adalah sifat Shiddiq, Amanah, Fathonah, Dan Tabligh. Penelitian ini bertujuan untuk: (1) mengetahui strategi guru dalam pembentukan karakter Nubuwwah pada siswa di Aqobah International School Jombang (2) mengetahui implikasi dari strategi guru dalam pembentukan Karakter Nubuwwah pada siswa di Aqobah International School Jombang (3) mengetahui faktor-faktor pendukung dan penghambat dalam pelaksanaan strategi pembentukan karakter Nubuwwah. Penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian analisis deskriptif. Teknik pengumpulan data dalam penelitian ini berdasarkan wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan teori dari Miles and Huberman. Hasil dari penelitian ini menjelaskan bahwa : (1) strategi yang dilakukan guru baik di bidang mata pelajaran maupun bidang kurikulum a. menggunakan media pembelajaran yang tepat, b.menggunakan keteladanan, c.melatih kedisiplinan siswa saat pembelajaran, d. menggunakan spesialisasi/ ekstrakurikuler sekolah, 5)Menjalin hubungan yang terbuka (2) Karakter Nubuwwah yang tercermin dari proses pembelajaran yakni Siddiq : Semangat kontribusi, jujur dalam berkarya, Amanah: Bertanggung jawab atas assignment atau tugas yang diberikan,tepat waktu Fathonah : Mampu mencerna materi (responsif), Tabligh : Komunikatif, saling membantu teman , (3) Faktor pendukung dari penerapan strategi guru dalam pembentukan karakter Nubuwwah pada siswa diantaranya kemudahan akses teknologi, sumber daya guru , manajemen sistem di Aqobah International School Jombang, sedangkan faktor penghambat diantaranya adalah berasal dari siswa itu sendiri dan masalah-masalah teknis dalam menerapkan strategi tersebut.